Obesity: the silent pandemic - Kaur, Ekjot; Kaur, Prabhjeet (International Journal Of Community Medicine And Public Health, 2023)
The overall prevalence of obesity worldwide has approximately tripled between 1975 and 2016. In 2016, 13% of the world’s population aged 18 and above (11% men, 15% women), were found to be obese.